2022
DOI: 10.1038/s41390-021-01891-y
|View full text |Cite
|
Sign up to set email alerts
|

A specialized multi-disciplinary care program for children with sepsis and multiple organ dysfunction-associated immune dysregulation

Abstract: The complex physiology and medical requirements of children with sepsis and multiple organ dysfunction syndrome (MODS) challenge traditional care coordination models. While the involvement of multiple clinical subspecialty services is often necessary to support different care processes and individual organ system dysfunctions, it can also delay the diagnostic process, monitoring, and treatment. The logistics of coordinating with many specialty providers for critically ill patients are challenging and time cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…In particular, the logistics of navigating multi-disciplinary care were often felt to be challenging and frustrating, with fractured communication between departments, an inability to establishing lasting therapeutic relationships and a lack of support for medication adherence appearing to influence the patient’s psychosocial functioning. Similar findings have been identified in patients with complex needs [ 88 ] and children with sepsis and multiple organ dysfunction-associated immune dysregulation [ 89 ]Whilst evidence from the qualitative studies reported several unmet healthcare needs in this clinical population, no quantitative findings could confirm these findings. In light of the multitude of healthcare challenges outlined throughout this review, future research should seek to obtain insight into the care provided to individuals with advanced oesophago-gastric cancer, in relation to the reported unmet care needs and satisfaction with the care provided.…”
Section: Discussionsupporting
confidence: 64%
“…In particular, the logistics of navigating multi-disciplinary care were often felt to be challenging and frustrating, with fractured communication between departments, an inability to establishing lasting therapeutic relationships and a lack of support for medication adherence appearing to influence the patient’s psychosocial functioning. Similar findings have been identified in patients with complex needs [ 88 ] and children with sepsis and multiple organ dysfunction-associated immune dysregulation [ 89 ]Whilst evidence from the qualitative studies reported several unmet healthcare needs in this clinical population, no quantitative findings could confirm these findings. In light of the multitude of healthcare challenges outlined throughout this review, future research should seek to obtain insight into the care provided to individuals with advanced oesophago-gastric cancer, in relation to the reported unmet care needs and satisfaction with the care provided.…”
Section: Discussionsupporting
confidence: 64%
“…Отже, комплексне лікування хворих на сепсис немовлят потребує, з одного боку, ін-дивідуалізованого підходу і менеджменту з урахуванням біомаркерів, а з іншого -міждисциплінарного комплексного бачення проблем поліорганної невідповідності [21], у тому числі синдромів гіперзапалення, тяжкого мультисистемного запального синдрому з індивідуальним лікуванням цих складних розладів.…”
Section: вступunclassified
“…Swigart et al recently reported on the successful development of a multidisciplinary, inpatient consult service for children with sepsis and multiorgan dysfunction syndrome. 10 During the coronavirus disease 2019 (COVID-19) pandemic, many pediatric institutions developed a similar multisubspecialty approach to the management of children with multisystem inflammatory syndrome. The development, structure, and scope of these types of collaborative and multidisciplinary teams vary across institutions.…”
Section: Dr Degar Et Al Replymentioning
confidence: 99%